Identification of the bacterial isolates in neonatal septicaemia and their antimicrobial susceptibility in a tertiary care hospital in Uttarakhand, India: a retrospective study - Pandita, Neerul; Wasim, Sanober; Bhat, Novneet Kumar; Chandra, Vipan; Kakati, Barnalli (International Journal of Contemporary Pediatrics, 2016)
Background: Neonatal sepsis refers to systemic bacterial infection documented by positive blood culture in the first four weeks of life and is one of the four leading causes of neonatal mortality and morbidity in India. This study was a retrospective study to identify the bacterial isolates in neonatal septicaemia and their antimicrobial susceptibility in a tertiary care hospital in Uttarakhand, India from January 2013 to June 2015. Methods: Blood culture in newborns with clinical sign of septicaemia was retrospectively studied. Antimicrobial susceptibility testing was performed by Kirbuay -bauer disc diffusion susceptibility method in accordance to clinical laboratory standard institute guidelines (CLSI). Results: 10.3% (124 /1200) cases of septicaemia could be confirmed by blood culture. Of these Gram negative could be isolated in (62%) of cases and (38%) were of gram positive isolates. Kliebsiella was the predominant pathogen (42.8%) among the gram negative pathogens followed by E coli (18.1%). CONS (57.4%) was the predominant gram positive pathogen. Of the Gram positives isolates 6% were methicillin resistant S.aureus (MRSA). Polymyxin (77.8%) and tigecycline (72%) were most effective drugs against gram negative isolates were as gram positive organisms showed maximum sensitivity to vancomycin (90%) and linezolid (87%). Conclusions: This study highlights the growing resistance to commonly used antibiotics; ampicillin, penicillin, ceftriaxone and ceftazidime and also highlights the importance of kleibsiella and Staphylococcus aureus as principal organism responsible for neonatal sepsis in tertiary care settings.